2021
DOI: 10.1016/j.stemcr.2021.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Robotic high-throughput biomanufacturing and functional differentiation of human pluripotent stem cells

Abstract: Efficient translation of human induced pluripotent stem cells (hiPSCs) requires scalable cell manufacturing strategies for optimal selfrenewal and functional differentiation. Traditional manual cell culture is variable and labor intensive, posing challenges for highthroughput applications. Here, we established a robotic platform and automated all essential steps of hiPSC culture and differentiation under chemically defined conditions. This approach allowed rapid and standardized manufacturing of billions of hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…CEPT improves cell survival, prevents cellular stress, leads to optimal cell aggregation, reduces experimental variability, results in overall improved cell differentiation and tissue-specific 3D architecture. The four-part CEPT cocktail is also more cost-efficient than 10 µM Y-27632 and other reagents (Chen et al, 2021, Tristan et al, 2021). Hence, the use of CEPT promotes standardization, optimal biological outcome, and should help with utilizing next-generation EB and organoid models suitable for translational applications and drug discovery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CEPT improves cell survival, prevents cellular stress, leads to optimal cell aggregation, reduces experimental variability, results in overall improved cell differentiation and tissue-specific 3D architecture. The four-part CEPT cocktail is also more cost-efficient than 10 µM Y-27632 and other reagents (Chen et al, 2021, Tristan et al, 2021). Hence, the use of CEPT promotes standardization, optimal biological outcome, and should help with utilizing next-generation EB and organoid models suitable for translational applications and drug discovery.…”
Section: Resultsmentioning
confidence: 99%
“…Cell aggregation and self-organization have been used for over a century to study the simple metazoan Hydra (Layer et al, 2002). More recently, these tissue engineering methods have been employed to generate various stem cell-based 3D models such as EBs, neurospheres, and organoids from different developmental lineages (Eiraku et al, 2008; Keller, 1995; Lancaster et al, 2013; Quadrato et al, 2017; Reynolds and Weiss, 1992; Sato et al, 2009; Singec et al, 2006; Tristan et al, 2021; Tsankov et al, 2015). Culturing hPSCs is particularly challenging as these cells are inherently sensitive to environmental perturbations and require special conditions, cell culture media, and reagents.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported on the automation of iPS cell culture, addressing automation of iPS cell reprogramming, clonal isolation, induced clonal stability, and differentiation towards several tissues ( Haupt et al, 2012 ; Konagaya et al, 2015 ; Paull et al, 2015 ; Coston et al, 2020 ; Elanzew et al, 2020 ; Tristan et al, 2020 ). Our work contributes to these efforts by providing a novel approach for the generation and differentiation of iPS cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…For NK cell ACT, iPSCs offer advantages in key areas of manufacturing and translation, promising to provide a cell source for biologically young, "off-the-shelf", and bioengineered enhanced iPSC-NK cells. With iPSCs already making an impact in the clinic, iPSC-NK cells can benefit from advances in manufacturing (162) and genome engineering strategies (163) to create iPSC-NK cells that have contextdependent functions and enhanced potency and specificity. For NKEVs, future work may soon confirm that their composition can be genetically controlled, and, similarly to enhanced NK cells, this could lead to the development of enhanced NKEVs the potential to be purified as a stand-alone therapeutic or deployed as an addition to engineered iPSC-NK cells that can home to tumor sites and secrete enhanced NKEVs in situ.…”
Section: Discussionmentioning
confidence: 99%